Un ravissant souvenir de mon stage chez le laboratoire de Jérôme Lejeune. A delightful memory from my stay at Jerôme Lejeune’s laboratory - Drets, Máximo (Anales de la Facultad de Medicina, 2016)
For Number 2 of Volume 2 of AnFaMed we asked Prof. Máximo Drets to write a review article on the origins of clinical genetics and cytogenetics in Uruguay. He wrote the article starting with the development of world cytogenetics, followed by the development of cytogenetics in Uruguay. The direct contact with French researchers, specifically with Jérôme Lejeune, founder of modern human cytogenetics, and with his pupil, Roland Berger, was of utmost importance for Uruguayan scholarship holders. One of the first to be benefited, was Dr. Drets who worked as a collaborator in Lejeune’s laboratory, acquiring sufficient knowledge to be able to lead local development of human genetics. Several anecdotes of historical interest were not included in the original article; one of them is now published in the editorial space covering historical aspects.